HUBUNGAN PERKEMBANGAN ANAK DENGAN RISIKO GANGGUAN PEMUSATAN PERHATIAN DAN HIPERAKTIVITAS (GPPH) ANAK PRASEKOLAH DI TK MUTIARA HATI KLATEN TENGAH - Fitriana Noor Khayati; Esri Rusminingsih; Devi Permatasari; Reyhan (Universitas Muhammadiyah Klaten, 2024)
Attention Deficit and Hyperactivity Disorder (ADHD) is growing concern, as 5.4 million out of 6.1 million preschool student have ADHD. ADHD often occurs in children under 7 years old which can lead to child development disorders. The problem of child development disorders is a serious problem because it can affect children to continue their education. Therefore, is requires early detection of ADHD and child development disorders for prevention. The purpose of this study is to determine the relationship between child development and the risk of attention deficit and hyperactivity disorder (ADHD) of preschool children in Mutiara Hati Kindergarten School, Central Klaten. This type of research is quantitatively correlated with a cross sectional approach. The population of this study is students of Mutiara Hati Kindergarten Central Klaten, which was selected by the purposive sampling method, so that the total sample is 68. Hypothesis testing using spearman rho test with SPSS 25 tool. The instrument used in this research are Abbreviated Conners Rating Scale (ACTRS) and Developmental Pre-Screening Questionnaire (KPSP). The results of this study indicate that there is a relationship between child development and ADHD with a p-value of 0,004 (α=0,05) with a value r=0,346 which means a positive relationship between the two variables. The higher deviation the child's developmental, the higher the risk of ADHD, conversely the lower the deviation of child's developmental, the lower the risk of ADHD